Study on Failure Mechanism and Phase Transformation of 304 Stainless Steel during Erosion Wear - Youjun Ye; Jing Li; Xingxing Lv; Lin Liu (Metals, 2020)
In this paper, the failure mechanism and phase transformation process of 304 stainless steel during the erosion wear process were studied with a rotary erosion wear test device. The surface morphologies of the worn 304 stainless steel were investigated by scanning electron microscopy (SEM). The metallographic structures of the nonworn and worn 304 stainless steel were analyzed by optical microscope (OM) and transmission electron microscopy (TEM). In addition, the surface hardness on different areas of the sample was also measured. The results demonstrated that the failure mechanism of 304 stainless steel during the process of erosion wear was cutting and spalling caused by plastic deformation. The high-density dislocations move along the slip planes between slip lines, which resulted in the formation of martensite phase between the slip lines. Meanwhile, the martensitic transformation on the worn surface caused by severe plastic deformation was the coordination of dislocation martensite and twin martensite.